Moral value reflected by the main character in heroes (2020) movie - Kamajaya, I Kadek Putra; Candra, Komang Dian Puspita; Ariyaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2022)
This study is entitled “Moral Values Reflected by the Main Characters in Heroes (2020) Movie. The aim of this study was to analyze and find out the types of moral value reflected by the main character in Heroes (2020) Movie. This study used the theories proposed by Audi (2007) to analyze the types of moral values and supported the theory by Klarer (2004) to analyze the character. Descriptive qualitative method was used in the data analysis while the method of observation was used to collect the data. The result of this study found that there are 6 data containing moral values occurring in the movie reflected by the main characters as follows. (1) Virtue consists of Courage, Generosity, Honest, and Loyalty (each of types occurred 1 times with 16, 6%), 2) Kantian and Intuitionism and 3) Utilitarianism also occurred 1 times with 16, 6%). The frequency of the appearance of moral values by the main character is balanced.